Leading education systems - Brown, Stephen; Duignan, Patrick (Emerald Publishing Limited, 2021)
Vibrant, quality, inclusive, and performing education systems remain a constant aspiration for all countries and educational stakeholders, and are more important than ever given the uncertain and disrupted times in which we live. Ground-breaking and timely, Leading Education Systems explores the nature, dispositions and context of the leadership of schooling systems. Acknowledging the once-in-a-lifetime stimulus of a pandemic, this timely edited collection highlights the opportunity we have for comprehensive and complex new discussions around education systems. Drawing on the perspectives of a diverse range of global thought leaders, academics and scholar-practitioners, this text is a springboard for the re-imagination of education system leadership. Supporting and fortifying leaders to question traditional models of system leadership, Brown and Duignan envision how system leaders might act in collaboration with others to lead differently. Their book is a must-have call to action for education stakeholders to lead us into a new and different age, and a sustainable future.